Impact of Short Pregnancy Interval on Feto-Maternal Outcome in Women with Previous caesarean section - Zeenat, Quratulain Shahzad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Short inter-pregnancy interval has been associated with an increase risk of adverse pregnancy outcomes after caesarean section. Method: A descriptive study, carried out in tertiary care hospital on total 63 numbers of women for a duration of six months with short inter-pregnancy interval and history of previous caesarean section. Results: Among women with history of previous LSCS (n=63), mean age 26.5±4.6 years, gestational age 37.8±2.2 weeks, recommended IPI (>18 months) was observed only in 15.9% women. Most common indications for current C-section were irregular pain (20.6%), term women (12.7%), and fetal distress (11.1%). Occurrence rate of uterine scar dehiscence was 33.3%, preterm birth 19.0%, low birth weight 15.9%, and uterine rupture 3.2%. Frequency of uterine scar dehiscence was significantly higher in IPI ≤6 months than in >6 months (66.7% vs. 33.3%; p 0.040); and in IPI ≤12 months than in >12 months (81% vs. 19%; p 0.036). All two cases of uterine rupture were observed in IPI ≤6 months but the difference was not statistically significant. Frequency of preterm birth was insignificantly higher in IPI ≤18 months than in >18 months (66.7% vs. 33.3%; p 0.086). Conclusion: We found elevated risk of uterine scar dehiscence, uterine rupture, low birth weight babies along with preterm births. Keywords: IPI (Inter-pregnancy interval), LSCS (Lower Segment Cesarean Section), Scar dehiscence, Low Birth Weight.